Implementasi Teknik Foley Dan Voice Over Dalam Pembuatan Film Dokumenter Wonderful Batam - Julio Tathohud Putera Kuba; Happy Yugo Prasetya; Denta Masiddhakarya Safira Kinayoman (Politeknik Negeri Batam, 2021)
Wonderful Batam documentary is a documentary video featuring 3 tourist destinations in Batam city, namely entertainment tourism, culinary tourism and religious tourism. Movie goers and creators often only put visual elements forward in filmmaking. In fact, in a film there is also an audio element that also plays an important role in supporting the portrayal of emotions and messages that want to be presented in the film. The purpose of this research is to implement foley and voice over techniques on audio making in the documentary Wonderful Batam, this is done to clarify the information and atmosphere that occurs in the video as well as improve the audio in the documentary Wonderful Batam, which focuses on maximizing foley techniques and voice over in the making. Wonderful Batam documentary filmmaking method uses Villamil-Molina method consisting of 5 stages of development, prep roduction, production, post production, and delivery where foley and voice over techniques are performed at the post production stage. Wonderfull Batam documentary was then conducted alpha testing to media and beta experts to 30 respondents. It is hoped that this research will introduce foley and voice over techniques to readers who are studying the topic of filmmaking